Endobronchial hamartoma mimicking malignant lung tumor contralateral endobronchial metastasis: A case report. Issue 49 (December 2017) - Chen, Sheng-Song; Zhou, Hong; Tong, Bo; Yu, Ling-Ling; Fan, Si-Si; Xiao, Zu-Ke
Abstract: Rationale: Endobronchial hamartoma, the most common benign lung tumor, is located in the bronchus, and it easily mimics lung cancer or bronchial metastasis. Endobronchial hamartoma can cause coughing, hemoptysis, and pulmonary infection; thus, it should be treated right away by surgery or fiberoptic bronchoscopy. Patient concerns: We report a rare case of endobronchial hamartoma in which the clinical symptoms and imaging overlapped strongly with malignant lung tumor contralateral endobronchial metastasis. Diagnoses: Endobronchial hamartoma coexisting with a malignant lung tumor. Interventions: Fiberoptic bronchoscopy was conducted, and the pathologic diagnosis was hamartoma. A second fiberoptic bronchoscopy was conducted, and fine-needle aspiration cytology of the enlarged lymph nodes indicated squamous cell carcinoma. Outcomes: The clinical symptoms were relieved, and the treatment options were docetaxel, cis-dichlorodiamineplatinum, and endostatin. Lessons: Fiberoptic bronchoscopy needs to be guided by imaging and can be considered an effective method for the diagnosis of endobronchial hamartoma.